Rekonsiliasi Sosial: Satu Kerangka Analisis dari Teori Konsensus - Ulber Silalahi (Centre for Public Policy and Management Studies, 2008)
This article discusses social reconciliation and consensus. The analysis covers social solidarity and collective awarness and how do they relate to modern society in general and Indonesian society in particular. The discussion pn social reconciliation and consencus specifically focus on Indonesia's post new order era when to a certain extent anomic has existed.Keywords: concensus, social reconciliation